THE PERCEPTION OF PROFESSIONALS IN THE FINANCIAL ACCOUNTING FIELD FROM ROMANIA REGARDING THE DIGITALIZATION OF THE ACCOUNTING PROFESSION - PODOABĂ LUCIA; ARMANCĂ LUCICA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
The use and implementation of digital technologies related to the current economy will allow to the professionals in the financial and accounting field to become creators of added value, through the quality services provided. However, the digital revolution brings important changes in the work of the specialist in this field, forcing him to continuously improve his skills. Taking into account the implications and consequences of the digitization of the accounting profession, this paper actually represents a case study regarding the perception of accounting professionals regarding the future of the accounting profession in the digital economy. Its final conclusions highlight the fact that the accounting profession is not dominated by information technology, but is influenced by the level of digitization of the economic environment